2016
DOI: 10.1136/bcr-2015-214206
|View full text |Cite
|
Sign up to set email alerts
|

Primary high-grade neuroendocrine carcinoma emerging from an adenomatous polyp in the setting of familial adenomatous polyposis

Abstract: Familial adenomatous polyposis (FAP) is a rare inherited syndrome that is characterised by innumerable adenomas of the colon and rectum, a high risk of colorectal cancer and a variety of extracolonic manifestations. FAP presents as hundreds to thousands of colonic adenomas beginning in adolescence. The syndrome is associated with less than 1% of all colorectal cancer cases, but there is a nearly 100% lifetime risk of colorectal cancer in individuals with FAP. This case demonstrates a 60-year-old man with FAP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, the lack of mutations in ATRX, DAXX, MEN1, and TSC2 supports a distinctive molecular evolution for the NEC component in comparison to NET tumors[ 45 ]. Additionally, primary high grade NEC rarely occurs in patients with FAP in contrast to neuroendocrine hyperplasia and well differentiated NET supporting the theory that the evolution of NEC is distinct from NET in these mixed tumors[ 52 ].…”
Section: Discussionmentioning
confidence: 55%
“…However, the lack of mutations in ATRX, DAXX, MEN1, and TSC2 supports a distinctive molecular evolution for the NEC component in comparison to NET tumors[ 45 ]. Additionally, primary high grade NEC rarely occurs in patients with FAP in contrast to neuroendocrine hyperplasia and well differentiated NET supporting the theory that the evolution of NEC is distinct from NET in these mixed tumors[ 52 ].…”
Section: Discussionmentioning
confidence: 55%
“…It should be noted that other hereditary conditions including MEN1 & 2, VHL, and Neurofibromatosis Type 1 are syndromes with well-established potential for neuroendocrine tumor development [8]. A sparse number of case reports describing NETs in the setting of FAP have been noted including those by Detweiler et al, Camp et al, and Venu et al [9][10][11]. In addition, Weidner et al reported a case of NET in the setting of MUTYH Adenomatous Polyposis, an autosomal recessive disorder with a similar predisposition to adenomatous development within the gastrointestinal tract [12].…”
Section: Discussionmentioning
confidence: 99%
“…Both C- and R-MiNENs involve mixed adenocarcinoma-NECs and mixed adenocarcinoma-NETs [16]. Though several CR-NENs have been reported in patients with familial colorectal cancer syndromes, including Lynch syndrome [65, 66] and familial adenomatous polyposis [67], the exact role of these syndromes in CR-NEN development remains to be elucidated.…”
Section: Classification Based On Locationmentioning
confidence: 99%